ФОРМУВАЛЬНЕ ОЦІНЮВАННЯ ЯК КЛЮЧОВИЙ ЧИННИК ЯКІСНОЇ ОСВІТИ В НУШ - Предик, Аліна Анатоліївна (My University, 2022)
The article reveals the peculiarities of formative assessment in the conditions of the New Ukrainian School; functions, tasks, methods and techniques of formative assessment of junior high school students are analyzed.
Keywords: контроль; оцінювання; формувальне оцінювання; методи формувального оцінювання; техніки оцінювання